A randomized, open-label, two-period crossover study to evaluate the bioequivalence and food effect between two formulations of regorafenib in healthy adult participants - Li, Yan; Qi, Lu; Yang, Caixia; Zhao, Na; Wang, Xinghe (Frontiers in Pharmacology, 2025)
BackgroundThis research aimed to compare the bioequivalence of a test formulation (regorafenib produced by Beijing SL Pharmaceutical Co., Ltd.) with a reference formulation (the original drug Stivarga®) in Chinese healthy subjects under fasting conditions and two postprandial states: after low-fat and high-fat meals.MethodsThe research design was a randomized, open-label, two-period crossover trial involving a single 40 mg oral dose. Three separate studies were conducted. Study 1 enrolled 64 subjects who were dosed under fasting conditions; Study 2 involved 76 subjects dosed after a low-fat breakfast; and Study 3 also involved 76 subjects dosed after a high-fat breakfast. Plasma concentrations of regorafenib and M-2 were determined using a liquid chromatography-tandem mass spectrometry (LC-MS/MS) method. The primary endpoints were the peak plasma concentration (Cmax), the area under the concentration-time curve from time 0 to 168 h (AUC0–168h), and the extrapolated area under the curve from time zero to infinity (AUC0–∞) of regorafenib, with pharmacokinetics (PK) parameters of the metabolite M-2 serving as reference data.ResultsThe results showed that, under fasting, post-low-fat meal, and post-high-fat meal conditions, the 90% confidence intervals (CIs) of geometric mean ratios (GMRs) for Cmax of test to reference regorafenib were 96.39%–114.94%, 93.81%–106.67% and 94.23%–107.21%, respectively. For AUC0–168h were 88.40%–102.04%, 92.40%–102.97% and 92.50%–102.60%. For AUC0–∞ were 85.86%–100.01%, 90.26%–101.79% and 90.15%–101.36%. All of these fell within the 80.00%–125.00% range, meeting the equivalence criteria. Food intake had some impact on the PK parameters of regorafenib, but the effect was minor. Administration of a single 40 mg dose of regorafenib to healthy subjects demonstrated good safety and tolerability.ConclusionUnder different dietary conditions, a single oral dose of 40 mg of generic drug regorafenib was bioequivalent to the original drug Stivarga® in healthy Chinese subjects, and the food effect was limited.Clinical Trial Registrationhttp://www.chinadrugtrials.org.cn/, identifier CTR20210575, CTR20210576, CTR20223278.